2008
DOI: 10.1039/b805164j
|View full text |Cite
|
Sign up to set email alerts
|

Click chemistry step growth polymerization of novel α-azide-ω-alkyne monomers

Abstract: A novel step growth polymerization A-B strategy based on the click chemistry polyaddition of tailor-made alpha-azide-omega-alkyne low molar mass monomers was developed, leading to polytriazole (co)polymers with tunable structures and properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
74
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 17 publications
3
74
1
Order By: Relevance
“…[3][4][5] From the viewpoint of polymer synthesis, to say nothing of the polyaddition via click chemistry, [6][7][8][9][10][11] polymers possessing clickable pendant groups 12,13 and/or end-functionalities [14][15][16] have attracted researchers' attention, as such polymers can be used as 'building blocks' for syntheses of highly functionalized polymers, 17,18 construction of sophisticated topology, 19,20 and surface modification 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] From the viewpoint of polymer synthesis, to say nothing of the polyaddition via click chemistry, [6][7][8][9][10][11] polymers possessing clickable pendant groups 12,13 and/or end-functionalities [14][15][16] have attracted researchers' attention, as such polymers can be used as 'building blocks' for syntheses of highly functionalized polymers, 17,18 construction of sophisticated topology, 19,20 and surface modification 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Copper-catalyzed azide-alkyne cycloaddition (CuAAC) was selected for the step-growth chemistry because it has been shown to be an effective tool for macromolecular ligation. [84][85][86][87][88][89][90][91][92] In particular, Matyjaszewski and co-workers [93] and Drockenmuller and co-workers [94,95] demonstrated that step-growth CuAAC polymerizations proceed generally in high yields. This aspect was also verified in our study.…”
mentioning
confidence: 99%
“…An explanation of this effect based on the odd-evens reduction in crystallinity has been previously used in polyesters, where monomers from odd-chain length exhibit reduced enthalpies of melt and crystallization [37]. The density of triazole hydrogen bonding within a polymer has previously been demonstrated to be a factor influencing the glass transition temperature of polymers and dictating many thermal properties as well [38]. In the study by Binauld et al, monomers with equal carbon numbers were synthesized with both ester and ether linkages then polymerized into polytriazoles containing only ether linkages, polytriazoles with ester linkages only, and a copolymer consisting of both.…”
Section: Resultsmentioning
confidence: 99%